Effects of Dietary Paddy Rice on Growth Performance, Plasma Biochemical Parameters, Carcass Traits, and Breast Meat Quality in Geese - Z Liu; Q Xie; Y Chen; J Xue; X Huang; Y Luo; Q Wang; C Wang (Brazilian Journal of Poultry Science)
ABSTRACT This study was conducted to investigate the effects of dietary paddy rice on the performance of geese. A total of 210 28-day-old geese were randomly allotted to 5 treatment groups with 7 replicates of 6 geese each. The geese were raised for 42 days on feed with 0 (control), 30%, 40%, 50%, and 60% dietary paddy rice inclusion. The results showed that dietary paddy rice increased body weight, average daily feed intake, and average daily gain of geese (p<0.05), but did not influence feed/gain ratio (p>0.05). Increasing dietary paddy rice levels decreased the plasma total bilirubin, direct bilirubin, and indirect bilirubin content of geese (p<0.05). The percentage of carcass, half-eviscerated yield, and eviscerated yield in geese were increased as dietary paddy rice increased (p<0.05). The dietary paddy rice did not affect the breast meat quality of geese (p>0.05). In conclusion, paddy rice could increase the growth performance, and had no negative effects on plasma biochemical parameters, carcass traits, and breast meat quality of geese from 28 to 70 d of age. We showed that paddy rice can be used up to a concentration of 60% in the geese diets.